Democracy In Slovenia: Slovenia’s Entry Into The European Union After The Disintegration Of Yugoslavia - Hiswi, Putti Ananda (Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
After the disintegration of Yugoslavia, Slovenia made changes in its ideology and political system to become part of the European Union. However, as a newly independent country, Slovenia faces an unfinished successional political transition. Undertaking a democratic system shift will cause Slovenia to face several challenges: accepting and implementing new democratic laws, introducing a liberal economy with free initiative, and achieving national sovereignty as an independent country. Apart from being a newly independent country, Slovenia also has a history of war with Italy when it was under Yugoslavia during the Second World War. These conditions make Slovenia’s entry into the European Union problematic. This article aims to understand Slovenia’s policy transition process after the disintegration of Yugoslavia and its consideration to join the European Union. This article uses qualitative methods with data and literatures collection from various official documents, books, journals, and online news which discuss integration process and democracy implementation in Slovenia related to its integration to European Union. This article concludes that Slovenia’s decision to join the European Union - despite its position as a newly independent country and the history of war with Italy - was due to the belief that a common liberal democratic system could help open relations with fellow democracies. The similarity of this system can be seen from the application of the three pillars of liberal democracy in democratic peace theory. The theory postulates that when the three pillars are applied, liberal countries will not go to war with each other